Using thermal treatment for hardening corrosion-resistant coatings surfaced with a flux-cored wire containing BN-TiB2 -ZrB2 complex - E. N. Eremin; A. S. Losev; S. A. Borodikhin; A. E. Matalasova; I. A. Ponomarev (Омский научный вестник)
This study explores the metal of coating deposited by a highchromium flux-cored wire alloyed with a BN-TiB2-ZrB2 complex. We have investigated the changes in the durometric properties and fine structure of the coating after tempering and subsequent quenching. It is shown that the hardening of the metal of such a coating after quenching consists in formation of a complex composite structure with an iron-chromium martensitic matrix, a large amount of eutectic and particles of hardening complexes, which leads to an increase in hardness and wear resistance. It has been established that phase transformations in the metal of such coating are caused by the formation of an eutectic component based on chromium and iron borides, the framework structure and large number of dispersed titanium nitride particles up to 2,5 μm in size.